1972
DOI: 10.1007/bf00368963
|View full text |Cite
|
Sign up to set email alerts
|

Manometric Assessment of interstitial microalgae production in two estuarine sediments

Abstract: The potential production of estuarine interstitial microalgae from two tidal flats differing in sediment texture was determined manometrically. Sediment cores from the Southbeach tidal flat showed a maximum amount of productivity in the lower intertidal zone whereas sediment cores from Sally's Bend showed no production in this zone. The upper cm of sediment from both tidal flats had a higher amount of gross potential production than subsurface core sections. the sandy substratum from Southbeach had an estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1974
1974
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Annual production for the sediment community in the Zostera manna and the Ruppia maritima communities were 225 and 106 gC m-2, respectively. These values are in the range of previous reports for production in a variety of sediment types (Pomeroy 1959, Grontved 1960, Pamatmat 1968, Marshal1 et al 1971, Riznyk & Phinney 1972, Joint 1978, Zelder 1980, Rizzo & Wetzel 1985, Rizzo 1986). The contributions of the sedment to total annual production in these seagrass systems were 3 and 14 O/O which brackets the 8 % reported by Thayer et al (1975) for a Z. manna community in North Carolina.…”
Section: Discussionsupporting
confidence: 80%
“…Annual production for the sediment community in the Zostera manna and the Ruppia maritima communities were 225 and 106 gC m-2, respectively. These values are in the range of previous reports for production in a variety of sediment types (Pomeroy 1959, Grontved 1960, Pamatmat 1968, Marshal1 et al 1971, Riznyk & Phinney 1972, Joint 1978, Zelder 1980, Rizzo & Wetzel 1985, Rizzo 1986). The contributions of the sedment to total annual production in these seagrass systems were 3 and 14 O/O which brackets the 8 % reported by Thayer et al (1975) for a Z. manna community in North Carolina.…”
Section: Discussionsupporting
confidence: 80%
“…Most benthic microalgal studies from shallow or intertidal systems have found seasonal fluctuations in standing crop (Grantved 1960, 1962, Round 1960, Gargas 1970, Leach 1970, Gruendling 1971, Joint 1978, van den Hoek et al 1979, Colijn & Dijkema 1981, while others have found no seasonal fluctuations (Pamatmat 1968, Steele & Baird 1968, Riznyk & Phinney 1972, Cadee & Hegeman 1974, Riznyk et al 1978. Both situations were encountered in the results of the present study.…”
Section: Seasonal Fluctuationssupporting
confidence: 57%
“…Light penetration decreases with decreasing sediment particle size (Gomoiu 1967). Riznyk & Phinney (1972) found that sediment grain size was an important factor in determining benthic microalgal production, and Admiraal (1980) has emphasized that irradiance level may be important in determining the spatial distribution of benthic microalgae. Davis & McIntire (1983) found that the spatial patterns of sediment chlorophyll a were associated with sediment type in Netarts Bay, Oregon.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…4 . Propp et al (1980) with those of others investigating benthic primary productivity differences between coarse and fine-grained sediments in estuarine and marine ecosystems (Riznyk & Phinney 1972, Propp et al 1980. Ammonium was the dominant form of inorganic nitrogen released from sandy sediments, with elevated fluxes occurring in late spring and summer.…”
Section: A Mg/mmentioning
confidence: 97%